Effects of work-family conflict on job satisfaction and organizational commitment of bankers in South-West Nigeria (2009)
The study investigated the relationship between work-family conflict on job satisfaction and organization commitment of bank workers in southwestern Nigeria. The sample consists of 500 bankers (male =240, females =260) randomly selected from banks in South-Western Nigeria. Measures of demographic data, work-family conflict, Job satisfaction and organization commitment were administered to the bankers. Data collected were analyzed, using inter-correlational analysis. Results of the study indicate that work-family conflict had significant impact on the job satisfaction and organizational commitment of the bank workers .The implication of the findings is that bank executives, organizational psychologists and human behavior analysts and management should put in place conducive condition that can reduce the negative impact of work-family conflict on overall employee job satisfaction and organizational commitment.